Prevalence of Thyroid Peroxidase and Thyroglobulin Autoantibodies in the Swedish Population - Bergemann, Neele; Jonsdottir, Berglind; Nilsson, Anna-Lena; Lantz, Mikael; Lind, Alexander (Experimental and clinical endocrinology & diabetes, 2023)
Autoimmune thyroid disease (AITD) may be detected prior to clinical symptoms through the presence of autoantibodies against thyroid peroxidase (TPOab), thyroglobulin (TGab), or both.The present study aimed to develop a novel radiobinding assay (RBA) for TPOab and to determine the prevalence of TPOab and TGab in the Swedish population.Patient samples from 27 newly diagnosed Graves' disease patients in longitudinal follow-up and 124 AITD autoantibody-positive children in prospective follow-up for increased risk of type 1 diabetes were included to validate the novel RBA for TPO. The results of RBA were compared with those obtained by commercial radioimmunoassay (RIA) and electrochemiluminescence (ECL). Furthermore, 476 serum samples from adult blood donors and 297 from 13-year-old school children were analyzed for the presence of TPOab and TGab.Receiver operating characteristics analysis for the novel TPOab resulted in an area under curve (AUC) value of 0.82 (p<0.0001), a sensitivity of 77.8%, and a specificity of 91.9% in adult blood donors, and an AUC value of 0.70 (p<0.0001), a sensitivity of 53.2% and a specificity of 95.3% in the 13-year-old school children, respectively. TPOab levels in RBA correlated with both ECL (r=0.8950, p<0.0001) and RIA (r=0.9295, p<0.0001). The prevalence of TPOab and TGab was 6.3% and 7.6% in adult blood donors and 2.9 and 3.7% in 13-year-old school children.In conclusion, a novel RBA for the determination of TPOab was developed and validated with current methodologies. This study also reports an increasing prevalence of thyroid autoantibodies from adolescence to adulthood.